2008
DOI: 10.1021/pr800554w
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Natural Glycopeptides with Sugar Moiety-Dependent Antioxidant Activities Derived from Ganoderma lucidum Fruiting Bodies

Abstract: A water-soluble glycopeptide (PGY), fractionated and purified from the aqueous extract of the fruiting bodies of Ganoderma lucidum via two-step dialysis, anion-exchange and gel permeation chromatography, was constituted of two moieties of carbohydrate and peptide. Carbohydrate characterization with component analysis, methylation analysis, periodate oxidation, Smith degradation, enzymic hydrolysis, and IR and NMR experiments demonstrated that the carbohydrate moiety possessed a backbone of approximately thirty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 31 publications
0
21
0
3
Order By: Relevance
“…The SOD activities of these metal complexes were quantified using a modified nitro blue tetrazelium (NBT) assay system 62,63 . The NBT assay was based on the capacities of these metal complexes to inhibit the reduction of nitroblue tetrazolium (NBT) by photochemically generated superoxide anion radical in the presence of riboflavin.…”
Section: Esi-msmentioning
confidence: 99%
“…The SOD activities of these metal complexes were quantified using a modified nitro blue tetrazelium (NBT) assay system 62,63 . The NBT assay was based on the capacities of these metal complexes to inhibit the reduction of nitroblue tetrazolium (NBT) by photochemically generated superoxide anion radical in the presence of riboflavin.…”
Section: Esi-msmentioning
confidence: 99%
“…Wu and Wang (2009) reported that water soluble glycopeptides isolated from fruiting bodies of G. lucidum had the IC 50 towards DPPH…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…However, for a long time, western culture acknowledged only the nutritional and culinary values of some mushroom species [3]. Nevertheless, investigators around the world have recently become aware of their medicinal qualites and significant biological activities, including antimicrobial [4][5][6], antioxidative [7][8][9], antiinflammatory and antitumor [10], cardiovascular [11], antiparasitic, hepatoprotective and antidiabetic [12][13][14]. There are a great many medicines in the world based on bioactive compounds isolated from extracts of mushrooom sporocarps or mycelium [1], and specific mixtures of these extracts have been used to enhance immunity and stabilaze convalescence [15].…”
Section: Introductionmentioning
confidence: 99%